VEXAS syndrome in rheumatology practice: features from a multicenter cohort in north-east Italy - Bindoli, Sara; Morello-Pasin, Greta; Guidea, Irina; Padoan, Roberto; Iorio, Luca; Bixio, Riccardo; Orsolini, Giovanni; Maiolini, Federica; Lombardi, Sara; Lombardi, Sandra; Favero, Marta; Bernardi, Cristina; et al. (Frontiers in Immunology, 2025)
ObjectiveVEXAS syndrome (Vacuoles, E1 enzyme, X-linked, Autoinflammatory, Somatic) is a late-onset autoinflammatory disorder caused by somatic mutations in the UBA1 gene. It is characterized by systemic inflammation, a wide spectrum of rheumatologic features, including chondritis and inflammatory arthritis, dermatologic manifestations (e.g. neutrophilic dermatosis or vasculitis-like lesions), and hematologic abnormalities like macrocytic anemia and myelodysplastic syndrome. Due to its heterogeneity, diagnosis is frequently delayed. Early recognition of hallmark inflammatory symptoms, particularly by rheumatologists, is critical for timely diagnosis and management.MethodsWe conducted a retrospective analysis of 37 patients over the age of 50. Next-Generation Sequencing (Illumina HiSeq2500) was employed to assess mutations. Clinical, genetic, and demographic data were extracted from electronic medical records.ResultsTwenty patients [100% male; median age 73 years (IQR 67–77)] were confirmed to carry somatic UBA1 mutations. All patients exhibited constitutional symptoms (100%) and at least one rheumatologic manifestation, including chondritis (75%), arthralgia or arthromyalgia (50%), arthritis (30%), osteopenia or osteoporosis (15%), myalgia or myositis (10%), and tenosynovitis (5%). Dermatologic and hematologic abnormalities frequently co-occurred. Infectious complications were observed in 80% of patients and were a major contributor to overall morbidity.ConclusionThis study underscores the need for a phenotype-driven diagnostic approach to facilitate earlier identification of VEXAS syndrome. Our findings suggest that current estimates of prevalence in rheumatology settings may significantly underestimate the true disease burden. Improved awareness and interdisciplinary collaboration, particularly among rheumatologists, hematologists, and dermatologists, are essential to enhance recognition, diagnosis, and comprehensive care for individuals affected by this complex syndrome.